Penyelesaian Keterlambatan Pembayaran Kredit Di Bank Rakyat Indonesia Kantor Cabang Pembantu (KCP) Borong Kabupaten Manggarai Timur - Kade, Angelina Febriani; Jacob, Yossie M Y; Dju Bire, Chatryen M (Artemis Law Journal, 2025)
This study analyzes the obstacles and efforts to overcome late credit payments at BRI KCP Borong, East Manggarai Regency, using empirical legal research methods and a descriptive qualitative approach. The results of the study identified two groups of factors causing delays: (1) internal factors, including an ineffective monitoring system, complicated restructuring procedures, lack of customer education, and technical disruptions; (2) external factors in the form of business competition, emergencies, economic fluctuations, customer characteristics, and inappropriate use of credit. BRI KCP Borong implements a comprehensive strategy through preventive efforts (strict feasibility analysis, education, and digital services) and repressive efforts (gradual collection, restructuring, mediation, and litigation). The research findings indicate that a gradual approach in accordance with the Banking Law and the Civil Code can balance the protection of the rights of both parties, although the recording of OJK's SLIK remains a serious consequence for customers. This study recommends strengthening the synergy between improving the bank's internal system, increasing customer capacity, and improving regulations in order to create a more responsive and fair banking system.